ChemInform Abstract: Organocatalytic Asymmetric Condensation/Keto—Enol Tautomerization Tandem Reaction: Access to Cyclobutanone α‐Amino Acid Ester Derivatives. Issue 45 (23rd October 2014) - Frongia, Angelo; Melis, Nicola; Serra, Ilaria; Secci, Francesco; Piras, Pier Paolo; Caboni, Pierluigi
Abstract No configurational assignments given for the cyclobutanone α‐carbon.